Analisis Peran Kader terhadap Cakupan Imunisasi Dasar Lengkap di Posyandu Wilayah Kerja Puskesmas Kereng Bangkirai Palangka Raya - Septian Mugi Rahayu; Maria Adelheid Ensia; Evaririn Evaririn (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The coverage of child immunization in WHO member countries (World Health Organization) has reached 90%; it is estimated that 85% of babies worldwide have been immunized. But there are still 19.3% million babies and children who have not fully received vaccinations at risk of developing PD3I. In Central Kalimantan PD3I cases, namely tetanus neonatrum, 2 cases died with no immunization status, measles had 569 cases with 424 cases of non- immunization status, diphtheria had 2 cases with non-immunization status. For the City of Palangka Raya, the PD3I case is measles suspicion, 260 cases with 197 cases not immunized, diphtheria 1 case with immunization status, Kereng Bangkirai Community Health Center. There are 2 cases of measles suspected. This study aims to determine the relationship of the role of cadres with complete basic immunization coverage in infants aged 0-11 months at the Posyandu in Kereng Bangkirai Health Center, Palangka Raya City. The study used correlational research; the study design was cross-sectional with an accidental sampling technique, the number of respondents was 35. The results of Chi-Square analysis obtained a value of 0.003 <(α = 0.05), thenH1 was accepted, there was a relationship between the role of cadres with complete basic immunization coverage in infants aged 0-11 months at Posyanduin Kereng Bangkirai Health Center, Palangka Raya City. It can be concluded that the role of important cadres in complete basic immunization, especially in providing information and motivation about the importance of immunization to improve health status in the community. Research sites are expected to motivate parents to pay attention to the completeness of immunizations to their babies and provide information on the importance of immunization.